The Al-Buraq Uprising and the Position of the League of Nations in 1929 (Journal of the College of Basic Education, 2026)
This study examines one of the most pivotal events in modern Palestinian history: the Al-Buraq Uprising of 1929, recognized as the first popular armed confrontation against attempts to Judaize Jerusalem under the British Mandate. It sheds light on the political, social, and religious roots that fueled the conflict between Palestinians and Jews at the Al-Buraq Wall—known to Jews as the Western Wall—and the resulting international intervention through the formation of two investigative committees by the League of Nations. The research is structured into three main sections. The first discusses the Zionist practices and policies that intensified tensions and contributed to the outbreak of violence. The second reviews the League of Nations' initial response through the establishment of the British-led Shaw Commission, whose recommendations failed to address Arab grievances adequately. The third analyzes the second international committee established to assess the claims and rights of Muslims and Jews regarding the Al-Buraq Wall, based on legal principles and historical documents affirming Muslim ownership of the site. The study deeply explores the tensions resulting from British policies in Palestine and highlights how the international system of the time employed investigative mechanisms to manage, rather than resolve, the underlying injustices. It concludes that the Al-Buraq Uprising marked a significant turning point in the Palestinian national struggle, signaling the beginning of organized resistance to Zionist expansion and British colonial.